A dose of fructose induces oxidative stress during endurance and strength exercise - Fernandez, J. M.; da Silva-Grigoletto, M. E.; Gomez-Puerto, J. R.; Viana-Montaner, B. H.; Tasset-Cuevas, I.; Tunez, I.; Lopez-Miranda, J.; Perez-Jimenez, F. (Journal of Sports Sciences, 2009)
This study sought to compare the time course changes in oxidative state and glycemic behavior when glucose or glucose plus fructose are consumed before endurance and strength exercise. After two weeks on a controlled diet, 20 physically trained males ingested an oral dose of glucose or glucose plus fructose, 15 min before starting a moderate-intensity 30-min session of endurance or strength exercise. The combination resulted in four randomized interventions: glucose or glucose plus fructose + endurance exercise and glucose or glucose plus fructose + strength exercise, which were implemented consecutively in random order at 1-week intervals. Plasma concentration of lipoperoxides, oxidized LDL, reduced glutathione, catalase and glycemia were determined at baseline, during exercise and acute recovery. Following the ingestion of glucose plus fructose, lipoperoxides, catalase and reduced glutathione depletion were significantly higher than following consumption of glucose, for both endurance and strength exercise (P < 0.05). Oxidized LDL-c was higher after glucose plus fructose than after glucose alone in endurance exercise (P < 0.05). There was no difference in the glycemic peak between glucose plus fructose and glucose ingestion in endurance exercise trials. In strength exercise, the post-absorptive glycemic peak was less when the participants ingested glucose plus fructose than glucose (P < 0.05), and a second peak was found in the recovery phase of this group (P < 0.05). In conclusion, the addition of fructose to a pre-exercise glucose supplement triggers oxidative stress.